Mechanical Behavior of Aluminum Sandwiches Made by Laser Welding. (2015) - Barbieri, G.; Cognini, F.; Lapi, G.; Vivio, F.
Abstract: Aluminium sandwiches are interesting subcomponents for lightweight structures applied in rail cars for high speed. A method to realize aluminium sandwiches consists in welding sheets to elementary extruded profiles. Laser welding is the production technology that promises the better features in terms of quality and productivity. Thanks to concentrate energy and very small Heat Input (HI), the laser welding process minimizing the wide of the Heat Affected Zone (HAZ) and the distortions and allow high welding speed. In this work laser technique was applied to join a mock-up of a large aluminium sandwich panel. The mechanical behaviour of the assembled panel was investigated in the two main orthogonal direction of load by four point bending tests. Elastic-plastic FE Analysis confirm the results of bending tests and it is possible to appreciate the quality of welding process that produce joint strength and ductile. In fact in the both load direction it's possible to evaluate the plastic deformation on the welded beam without visible cracks in the welds. The data about the mechanical features of the welds for the FE analysis, about the 80% of the base materials, was achieved by tensile test on elementary but joint. The SEM fractography of the butt joint shows dimples in all the surface of the fracture, confirming the good quality and ductility of welds also in presence of some little micro porosity. The present paper is based on the achievements of the TRAIN Consortium within the research project SIFEG (Integrated freight transport rail-road), granted by the Italian Ministry of Economic Development for the Program "Industria 2015 – Mobilità Sostenibile".